Islamization of Accounting Policies as a Solution to the Ethical Problem in Accounting through Accounting Education - Saikou Gassama; Tjiptohadi Sawarjuwono; Hamidah Hamidah (Budapest International Research and Critics University, 2021)
There is a growing concern for accountant involvement in the continuous scandals which is due to the ethical judgments of certain accountants and amount of academics recommend that the school system is partly responsible. The ethical elements of accounting education were found to be inadequate, so there is a lack of meaningful attention to tackling accounting problems. In the first place, the purpose of this study is to highlight the importance of ethics in accounting education. Second, the paper argues that in the application of accounting ethics, specifically Islam, accounting education should concentrate on religious codes of ethics and values. Furthermore, this research explored the ethical viewpoint of Islam and how it gives some insights into the process of creating a more harmonized and ethical accountant. This study suggests the Islamization of the ethical concept of accounting as a solution to the ethical challenges the accounting profession is confronted with, in the form of the introduction of Islamic ethics in accounting curricula to be taught as part of the ethical accounting education method., the paper is a concept paper using other publications on the topic with the aimed of suggesting good system of accounting education that will produce accountants with excellent ethics.